(3ahGFOs - (3Ydj Hf eMeO Hf YHO GdYRjR Hf aJhM GdKYdHj GdTGaYqj, JGL GdOjf, GdeYQha H` GHf GdOQjge hH` GHf CHj GdNjQ,J (B762 (3g` s
(3ChdgG (B:s
(3CWhd CbdGe GdfGS Gdjhe GdCQefi dCfg SJg hKdGKhf MQa hGdbHWi EKfGf hKdGKhf s
(3BNQgG (B:s
(3Ke SbWJ YeOJgG heG YdjgG ai MQjb GddHGOjf hQhGb OGQ GdMLGQI hOGQ NOjLI ai ThGd SfI EKfjf hSJjf hNeSeGFg ai JPcQg GdUaOi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhd eNJdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B210 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B723s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs